Analisis Usability Website Sistem Informasi Perpustakaan dengan System Usability Scale (SUS) dan Heuristic Evaluation (HE) - Fadly Safyuddin Maulana; Feri Wibowo; Abid Yanuar Badharudin; Agung Purwo Wicaksono (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to analyze the usability level of the Library Information System website of Muhammadiyah University of Purwokerto (SIPUS UMP) by combining two evaluation approaches, namely the System Usability Scale (SUS) and Heuristic Evaluation (HE). The evaluation was conducted by involving 30 active UMP student respondents for the SUS method and 5 expert evaluators from various professional backgrounds for the HE method. The HE evaluation results showed that the most significant problem was in the Help and Documentation aspect with the highest Severity Rating score of 3.10, while the Aesthetic and Minimalist Design aspect had the lowest score. Meanwhile, the results of the SUS method obtained an average score of 57.58%, which was categorized as Grade “D”, Adjective Rating “Good”, Acceptability “Marginal”, and Net Promoter Score (NPS) “Detractor”. These findings indicate that although the system is still acceptable to users, several improvements are needed in terms of appearance, documentation, and usage flow to improve the overall user experience. The combination of the HE and SUS methods in this study provides a comprehensive analysis both qualitatively and quantitatively as a basis for developing a more optimal system.